The role of the Ministry of Justice and the Ministry of Internal Affairs in the fight against the crime of human trafficking in Poland - Dworzecki, Jacek (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
This article outlines the role of the Ministry of Justice and the Ministry of Internal Affairs which due to their legal and doctrinal obligations deal with the issue of combating the crime of human trafficking in Poland.Furthermore, the text presents the concept of human trafficking found in the subject literature as well as legal instruments implemented with a view to combating this form of crime and the characteristics of the National Consultation Centre for Polish and Foreign Victims of Trafficking.
Keywords: handel ludźmi; Ministerstwo Sprawiedliwości; Ministerstwo Spraw Wewnętrznych; Polska